Effect of fluoride, casein phosphopeptide-amorphous calcium phosphate and sodium trimetaphosphate combination treatment on the remineralization of caries lesions: An in vitro study - Gonçalves, Francyenne Maira Castro [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Gomes, Leonardo Fernandes; Emerenciano, Nayara Gonçalves [UNESP]; Pessan, Juliano Pelim [UNESP]; Romero, Giovana Dornelas Azevedo [UNESP]; Cannon, Mark L.; Danelon, Marcelle [UNESP] (Elsevier, 2021)
Objective: To evaluate the effects of combination of treatments with fluoridated toothpastes supplemented with sodium trimetaphosphate (TMP) and casein phosphopeptide-amorphous calcium phosphate (MI Paste Plus®), on the remineralization of dental enamel. Design: Enamel blocks with artificial caries were randomly allocated into six groups (n = 12), according to the toothpastes: 1) without F-TMP-MI Paste Plus® (Placebo); 2) 1100 ppm F (1100 F), 3) MI Paste Plus®, 4) 1100 F + MI Paste Plus® (1100 F-MI Paste Plus®), 5) 1100 F + 3% TMP (1100 F-TMP) and 6) 1100 F-TMP + MI Paste Plus® (1100 F-TMP-MI Paste Plus®). Blocks were treated 2×/day with slurries of toothpastes (1 min). Furthermore, groups 4 and 6 received the application of MI Paste Plus® for 3 min. After pH cycling, the percentage of surface hardness recovery (%SHR); integrated loss of subsurface hardness (ΔKHN); profile analysis and lesion depth subsurface through polarized light microscopy (PLM), confocal laser scanning microscopy (LSCM), scanning electron microscopy (SEM), fluoride (F), calcium (Ca), phosphorus (P) concentrations in the enamel were determined. The data were analyzed by ANOVA (1-criterion) and Student-Newman-Keuls test (p < 0.001). Results: 1100 F-TMP-MI Paste Plus® group showed the best results of %SHR, ΔKHN and PLM (p < 0.001). F concentration was similar between the 1100 F, 1100 F-MI Paste Plus®, and 1100 F-TMP-MI Paste Plus® groups (p > 0.001). 1100 F-TMP-MI Paste Plus® group showed the highest concentration of Ca and P in the enamel (p < 0.001). Conclusion: The association of 1100 F-TMP and MI Paste Plus® led to a significant increase in the remineralization of initial carious lesions.
Keywords: CPP-ACP; Dental enamel; Fluoride; Phosphate; Remineralization